Teh Daun Kedondong (Spondias Dulcis L) terhadap Kadar Kolesterol Total pada Tikus Putih (Rattus Norvegicus) - Lale Budi Kusuma Dewi; Maruni Wiwin Diarti; Wiwin Safitri (Politeknik Kesehatan Kemenkes RI Jakarta I, 2017)
ABSTRACT Decreasing cholesterol levels is by consuming chemical drugs, namely statin drugs. Side effects of statins include muscle damage, muscle inflammation, and rhabdomyolysis, which is muscle pain accompanied by rupture of muscle protein. Therefore, other alternative herbal medicines are sought from plant compounds. One of the plants that can be used as an alternative medicine is kedondong leaf (Spondias dulcis L) because it contains compounds which are included in the group of antioxidants and polyunsaturated fatty acids which play an important role in decreasing total cholesterol levels. Objective: To determine the effect of giving kedondong leaf tea (Spondias dulcis L) to total cholesterol levels in wistar strains (Rattus norvegicus) white rats. Methods: Pre-Experiment Research design Postest-Only control Design with the data analysis technique used was the independent sample T Test. 10 male wistar strains of white rats (R. novergicus) used in this study were given kedondong leaf tea in the treatment group 1 time a day for 9 days by means of a round. The blood test method uses the Easy Touch GCU stick method. Results: Antioxidant group compounds (19.91%), polyunsaturated fatty acid compounds (47.51%). these compounds have an effect on the reduction in total cholesterol levels in the experimental wistar strain white rats (R. novergicus). Conclusion: Kedondong leaf tea (Spondias dulcis L) can be used as an alternative medicine to lower blood total cholesterol levels. Keywords: Kedondong leaf tea (Spondias dulcis L), total cholesterol level